Pemanfaatan Artificial Intelligence dan Literasi Digital untuk Pembelajaran Menulis di Sekolah Dasar - Rahmayantis, Marista Dwi; Pitoyo, Andri; Sujarwoko, Sujarwoko; Ramdani Putra, Chelya Ilham; Firmansyah, Achmad Fathoni; Gigik, Yolanda Rensia; Dinso, Junio Boy Smara; Rohmiati, Rohmiati; Pratiwi, Wahyu Adi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service programme aims to improve the writing skills of elementary school students through the integration of Artificial Intelligence (AI) and digital literacy. The method of implementing this activity uses training with the target, namely teachers at SDN Kampungdalem 1 Tulungagung, East Java. The evaluation instrument uses observation sheets and questionnaires which are then analyzed descriptively quantitatively and qualitatively. The results of this service showed that teacher competence and student writing skills improved through integrating AI and digital literacy in writing learning, as shown by an increase in the average writing score from 65.5 to 84.2. In addition, the success of this activity is supported by a holistic approach that combines teacher training, implementation assistance, and continuous evaluation.